Enantioselective Radical Functionalization of Imines and Iminium Intermediates via Visible-Light Photoredox Catalysis - Zhao, Jia-Jia; Zhang, Hong-Hao; Yu, Shouyun (Synthesis, 2021)
Visible-light photoredox catalysis has recently emerged as a powerful tool for the development of new and valuable chemical transformations under mild conditions. Visible-light promoted enantioselective radical transformations of imines and iminium intermediates provide new opportunities for the asymmetric synthesis of amines and the asymmetric β-functionalization of unsaturated carbonyl compounds. In this review, recent advances on the catalytic asymmetric radical functionalization of imines and iminium intermediates are summarized.1 Introduction2 Enantioselective Radical Functionalization of Imines2.1 Asymmetric Reduction2.2 Asymmetric Cyclization2.3 Asymmetric Addition2.4 Asymmetric Radical–Radical Coupling 3 Enantioselective Radical Functionalization of Iminium Ions3.1 Asymmetric Radical Alkylation3.2 Asymmetric Radical Acylation4 Conclusion
Keywords: asymmetric catalysis; photocatalysis; radicals; imines; iminium ions